Trends and Impacts of Real and Financial Globalization in the People's Republic of China and India since the 1980s - TN Srinivasan (World Scientific Publishing, 2013)
The dynamic process of integration of national economies has a long history, with two distinct waves: one, from the middle of the 19th century until its interruption with outbreak of the First World War in 1913 till the end of the Second World War in 1945. The second wave is ongoing dating from 1950. Two sub-processes of integration are usually distinguished. The first, called real integration related to flows of goods, services and factors across borders; the second called financial integration related to financial flows of claims on the nominal returns on financial assets. Financial integration has had a checkered history. Private financial flows, particularly debt flows, were evident in the first wave. During the second wave, debt flows, both intergovernmental and private banking lending were dominant during 1950–1980. Only after 1980, private non-debt flows particularly equity flows accelerated. This paper's primary focus is on the real and financial integration and their impact on trade, growth and poverty in the world's two dominant developing countries in emerging markets, namely the People's Republic of China (PRC) and India. The paper also discusses the reforms of institutional (domestic and multinational) foundations of real and financial integration, particularly the World Trade Organization, the World Bank, the International Monetary Fund, and the Group of 20. The impacts of the 2008–2009 financial crisis on the PRC and India are noted and the need for domestic financial sector reforms in both for them to cope with and respond to future financial crises is pointed out. Attention is drawn to the inadequacy of available analytical tools, in particular the absence of an appropriately integrated model of real and financial sectors to enable a meaningful assessment of the impact of financial shocks on the real sector.